Analysis of the effects of foreign direct investment in financial account of the balance of payments iraqi for 2003-2015 - حمود السامرائي, هناء عبد الغفار; عبدالكريم, امنة عبدالامير (Journal of Economics and Administrative Sciences, 2017)
The study aims to make an in-depth  analysis and the financial account components in the Iraqi balance of payments because it reflects the economic center of the country towards outside world, it also helps in making decision about monetary and financial policies, finance and foreign Trade the importance of FDI for Iraq lies as an important sources as wells provides advanced technology  and job chances, It also avoids the country negative effects of borrowing processes from abroad . for analyzing direct and indirect foreign investment on the balance of payments and financial account in a period between (2003 to 2015), a community and research sample have been selected, presented in CBI/ Balance of payments. Department, and followed up inserting income data from stakeholders, like banks and Iraqi securities market, in order to measure and calculate. FDI through transactions sorting that fell under this country, then transaction value has been fixed in the balance of payment as debtor, borrower activities.      The research methodology was based on a sample represented by guided evidences , issued by the International monetary of the balance of payment . find of preparation methods then a comparative study is made for the fifth edition in 1993 of world chide as well as sixth edition in 2009 the study has come to a conclusion that the direct foreign Investment flows isn’t succeeded amount of $m(1562.4) million dollar during the period (2007-2014) forming (7.4%) proportion of the total capitalism flows into Iraq which amounted to(21217,7) million dollar , and basically low , ranged (1.2%) of the total FDI flows to Arab countries in 2007 and (10.7%) in 2014 .  Which means that the financial obligations resulting from inflows are more than outflows .     The study has recommended depending and adapting certain means to ensure transmission of the effects of global economy by investment into local economy and real sections to ensure creating effects on financial account for the balance of payments at first than creating indirect effects on current account and account services through by influencing variable on economy as a total fixed capital formation as a production capacity that could be used to increase production and achieve growth .